Specialty cardiac nurses' work satisfaction is influenced by the type of coronary care unit: A mixed methods study - Judy Currey; Stephanie K. Sprogis; Liliana Orellana; Anusha Chander; Sharon Meagher; Rhoda Kennedy; Andrea Driscoll (BMC, 2019)
Abstract Background Many dedicated Coronary Care Units (CCUs) in Victoria, Australia, have been decommissioned and replaced with larger combined generic medical/cardiac precincts called hybrid units. Hybrid units are staffed with a low proportion of specialist critical care nurses. These changes may pose risks to nurse satisfaction and retention, and quality of patient care. The aims of this study were to explore specialist cardiac nurses' perceived work satisfaction across four CCUs, and differences in satisfaction between dedicated and hybrid CCUs. Methods This concurrent mixed methods study comprised two Phases in four Victorian CCUs (2 dedicated, 2 hybrid). In Phase 1, 74 specialist cardiac nurses completed the Professional Practice Environment (PPE) Scale. In Phase 2, 17 specialist cardiac nurses were interviewed to further explore elements of the PPE subscales. Descriptive, inferential (Phase 1), and content analyses (Phase 2) were performed. Results Survey participants' median age was 38 years (IQR 30, 45). The median PPE Scale score was 3.10 (IQR 2.90, 3.10) indicating high levels of satisfaction with their workplaces. Specialist cardiac nurses in one hybrid unit were significantly less satisfied compared with each of the other three units (p < 0.05). There were no significant differences in overall satisfaction or in any subscale of the PPE Scale between dedicated and hybrid units. Qualitative data revealed nurses in hybrid units felt they had less control over practice, lacked autonomy, had poor relationships with physicians, and experienced inadequate nurse leadership. Conclusions Specialist cardiac nurses' workplace satisfaction overall is high, with no significant differences between dedicated and hybrid CCUs. However, the structure of specialist cardiac units and NUM leadership skill level can impact nurses' satisfaction with their workplace and collegial relationships. Strong nursing leadership that is respectful of nursing expertise and places patient safety foremost positively impacts nurses' satisfaction. Further studies should assess the impact of the types of CCUs and NUM leadership on workforce factors such as nurse retention rates and patient outcomes such as adverse events.